Decreased glucose transporter densities, rate constants and glucose utilization in visual structures of rat brain during chronic visual deprivation - Duelli, Roman; Maurer, Martin H.; Kuschinsky, Wolfgang (Neuroscience letters, 1998)
The question was investigated whether local changes in glucose transporter densities and transport kinetics can occur when local cerebral glucose utilization (LCGU) is decreased in some brain structures. Unilateral visual deprivation was induced by monocular enucleation in 25 rats. After 1 week, the contralateral structures of the visual system were analyzed for (1) densities of glucose transporters Glut1 and Glut3 (immunoautoradiography), (2) LCGU (2-[14C]deoxyglucose method) and (3) local rate constants (3-O-[14C]methylglucose method). The ipsilateral structures served as controls. During chronic visual deprivation Glut1 and Glut3 densities, LCGU and rate constants were significantly decreased in some structures of the visual system and remained unchanged in others. These results indicate a moderate degree of downregulation of glucose transporters, LCGU and rate constants in the visual system during visual deprivation.
Gesehen am 28.05.2021